The Intersection of Sacredness and Archaeology
XIV, 351 p. 85 illus., 65 illus. in color.
Keywords: At the point of the often-contentious intersection of sacred site preservation and resource development, archaeology has a unique and valuable role. Archaeology has been criticized as a destroyer of sacred sites through the unbridled pursuit of knowledge through excavation or aiding unbridled development by failing to identify sacred sites. However, archaeology can act as a mitigator between the conflicting goals of preservation and development, while giving the indigenous a voice. At the heart of this mitigation is understanding the sacred: how it might be physically manifested, how those of diverse cultures understand it, and how it is effected by the laws and norms of diverse cultures. The purpose of this book is to enhance the discussion surrounding contemporary human interaction with our natural and cultural landscape. Its first goal is make this discussion more productive and less contentious by presenting and thus recognizing the cultural ways of knowing and perspectives of indigenous people. Its second goal is to foster the preservation of our scared landscape. As more and more of our physical landscape is being altered worldwide through rapid growth and development, the cultural landscape is also being changed and challenged. These changes often reflect the interests of some members of society, while the interests of others, including those of Native and Indigenous communities and many archaeologists, environmentalists and others who understand the importance of knowing the past, are disregarded. The latter group is dedicated toward preserving special places, and continuing to provide for Native people the ability to celebrate their traditions and focusing on defining the sacred landscape.